(3TYQ YR GdOjf eMeO Hf YHO Gddg Hf TQa GdOjfs - (3eLghds
(3ChdgG (B:s
(3GdZRGd GdeTfa (B*** (3gd dfG efg efUa , jhSaj GdLeGd eG (B*** (3bW jMcjg jhSas
(3BNQgG (B:s
(3eG TOi aj GdCjc beQj (B*** (3heG UGaMJ QjM GdUHG QhV GdNQGeGs
(3efbhd ef cJGH SeW GddBd dVjGA GdOjf ESeGYjd Hf eMeO Hf GdMSjf Hf CejQ GdeDefjf GdefUhQ HGddgs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdCOHs